The influence of territory planning and social development on strategic decisions in passenger transport development - Griškevičiene, Daiva; Griškevičius, Algirdas (Transport, 2004)
The main factors of space planning and social development which play an important role in making strategic decisions in passenger transportation have been analysed. A number of strategic aims based on major principles of territory transport planning have been formulated. The investigation made has shown that the operation of public transport is not closely connected with the main carcass of urban territories. This decreases the efficiency of public transport, making it less popular and competitive compared to automobiles. The creation of the strategy of public transport development for the period of its integration into the EU system requires the use of methods taking into account territory planning and social and economic development of the country. The integration of new territories into the existing transportation system, optimization of routes and the increase of transport service quality are aimed to provide higher living standards and better social and economic conditions for the inhabitants. The appropriate tactical decisions in planning the development of modern passenger transport may be made only if the harmonized and well‐grounded strategic aims are defined. First Published Online: 27 Oct 2010